2020
DOI: 10.48550/arxiv.2002.09956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De-randomized PAC-Bayes Margin Bounds: Applications to Non-convex and Non-smooth Predictors

Arindam Banerjee,
Tiancong Chen,
Yingxue Zhou

Abstract: In spite of several notable efforts, explaining the generalization of deterministic deep nets, e.g., ReLUnets, has remained challenging. Existing approaches usually need to bound the Lipschitz constant of such deep nets but such bounds have been shown to increase substantially with the number of training samples yielding vacuous generalization bounds [Nagarajan and Kolter, 2019a]. In this paper, we present new de-randomized PAC-Bayes margin bounds for deterministic non-convex and non-smooth predictors, e.g., R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Recently, Banerjee et al (2020) have developed novel deterministic bounds based on a de-randomization of a PAC-Bayes bound. Their bound is also based on the flatness of the minimum found after training (measured by Hessian eigenvalues), and also takes into account the distance moved in parameter space.…”
Section: Sensitivity-based Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Banerjee et al (2020) have developed novel deterministic bounds based on a de-randomization of a PAC-Bayes bound. Their bound is also based on the flatness of the minimum found after training (measured by Hessian eigenvalues), and also takes into account the distance moved in parameter space.…”
Section: Sensitivity-based Boundsmentioning
confidence: 99%
“…Neyshabur et al (2017);Banerjee et al (2020) provided some evidence that their PAC-Bayesian bounds correlates with true error when varying the data complexity. The authors are not aware of similar results for the other measures.• D.2 Neyshabur et al (2017); Banerjee et al (2020); Dziugaite et al (2020) have shown evidence that different sensitivity-based PAC-Bayesian bounds correlate with true error when varying the training set size.…”
mentioning
confidence: 99%